(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Thyroxine (T4) is important in gut development and maturation, and its use in treating hypothyroidism is becoming more popular. This study was conducted to evaluate the effect of thyroidectomy and thyroxine replacement on some gastrointestinal organs. Ten out of 20 thyroidectomised rats received 100pg/kgbw of T4 for five weeks to become euthyroid while the rest were left to become hypothyroid. Ten sham operated rats were made hyperthyroid by giving 100pg/kg.bw of T4 for five weeks, while the other ten sham operated rats served as control. 10mg/kg.bw intraperitoneal injection of ketamine was given as anesthesia for thyroidectomy and sham operation. At the end of the fifth week, the animals were sacrificed. Liver, stomach and small intestine were harvested and their morphological dimensions measured. Everted sacs were made from the small intestine for glucose transfer studies and slides for histomorphometry. There was no significant difference in the weights of the liver and stomach of the groups when compared with the control group. There was significant (p<0.05) increase in length and diameter but reduced wall thickness in the hyperthyroid small intestine; unlike that of hypothyroid which had significant (p<0.05) shorter length, decreased diameter but increased wall thickness. Villi length and crypt depth was higher in hyperthyroid (p<0.01) but smallest in the hypothyroid (p<0.05). Glucose transfer was lesser in the hypothyroid but greater in the hyperthyroid intestine. These findings show that hypothyroidism diminishes the morphological variables of absorption in the small intestine as a mechanism to reducing its transfer capacity, while thyroxine replacement increases these variables as mechanism to increasing intestinal transfer capacity.